2014
DOI: 10.1111/nmo.12467
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for dysphagia: a USA community study

Abstract: Background Dysphagia is considered an alarm symptom but detailed population-based data on dysphagia are lacking. We aimed to estimate in a representative US Caucasian population the prevalence of dysphagia and potential risk factors. Methods A modified version of the previously validated Bowel Disease Questionnaire was mailed to a population based cohort (n=7640) of Olmsted County, MN. Dysphagia was measured by one validated question “In the last year, how often have you had difficulty swallowing (a feeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 47 publications
(105 reference statements)
0
89
1
8
Order By: Relevance
“…we asked specifically about "repeated vomiting" rather than vomiting of any kind or due to an older study population in this study. Cho et al investigated self-reported "dysphagia" in an adult US Caucasian population and found that 3% had experienced "dysphagia" at least weekly within a recall period of 1 year [12]. In this study, 3.4% had experienced "difficulty swallowing" within the past 4 weeks.…”
Section: Strengths and Limitationsmentioning
confidence: 80%
“…we asked specifically about "repeated vomiting" rather than vomiting of any kind or due to an older study population in this study. Cho et al investigated self-reported "dysphagia" in an adult US Caucasian population and found that 3% had experienced "dysphagia" at least weekly within a recall period of 1 year [12]. In this study, 3.4% had experienced "difficulty swallowing" within the past 4 weeks.…”
Section: Strengths and Limitationsmentioning
confidence: 80%
“…Based on our results, esophageal motility disorder was common in PPI-resistant NERD patients complaining mainly of dysphagia. According to a report by Cho et al [18], 43% of 168 patients who had frequent dysphagia were found to have organic disease and had a significantly higher prevalence of GERD than patients without dysphagia [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is present in 3 to 9% in general population 1,2 , and up to 20% in older than 50 years 3 .…”
Section: Introductionmentioning
confidence: 99%